Reporting practices for unsolicited and secondary findings from next‐generation sequencing technologies: Perspectives of laboratory personnel. Issue 8 (6th June 2017) - Vears, Danya F; Sénécal, Karine; Borry, Pascal
Abstract : Interviews with laboratory personnel from Europe, Canada and Australasia showed varying practices in the reporting of unsolicited findings (UF) between laboratories. Some do not report UF while others report based on factors such as actionability, medical relevance or patient choice. Most laboratories are not currently actively searching for secondary findings. Our study highlights that laboratories are still grappling with decisions about which unsolicited findings to report from next generation sequencing and are calling for more guidance. Abstract: While next‐generation sequencing (NGS) has enormous potential to identify genetic causes of disease, the nature of the technology means that it can also identify additional information about the individual receiving sequencing that is unrelated to the original rationale for testing. Reporting these unsolicited findings (UF) to clinicians, and subsequently to patients, could lead to potentially lifesaving interventions. Most international guidelines provide limited specific recommendations as to whether these UF should be reported. Little research has been conducted exploring which of these variants are reported in practice. Twenty‐six interviews were conducted with 27 laboratory personnel, representing 24 laboratories in Europe (12), Canada (five), and Australasia (Seven) to explore their reporting practices. There is considerable variation between laboratories in the reporting of UF. While some limit their reporting to findings that are relevant to the clinical question, others report UF to varying degrees. In addition, most laboratory personnel interviewed said that their laboratories do not actively search for secondary findings in disease‐causing genes unrelated to the clinical question, such as those suggested by the American College of Medical Genetics and Genomics. Our study highlights that laboratories are still grappling with decisions about which UF to report from NGS and are calling for more guidance.